Tribological properties of self-mated SUS304 lubricated by palm methyl ester mixed lubricant at boundary lubrication. Issue 1 (March 2020) - Fuadi, Z; Faisal, M; Dirhamsyah, M; Tadjuddin, M; Kurniawan, R
Abstract: Due to environment and sustainability issues, it is important to reduce the use of petroleum based products in automotive and industrial application. One of the efforts is to use bio oils as base oil for lubricants. This paper presents the experimental results on the effects of palm methyl ester mixing in a conventional lubricant on the friction and wear characteristics of stainless steel SUS304. The friction tests were conducted using a ball-on-disk tribometer at boundary lubrication condition. Three kind of lubricants were prepared, i.e. commercial SAE40, and the mixture of 0.5% and 1% palm methyl ester into SAE40 lubricant. The prepared lubricants were designated as PME0, PME5, and PME10, in reference to 0%, 0.5%, and 1% palm methyl ester mixture in the SAE40 oil. Results shows that the addition of palm methyl ester in the lubricant has reduced the value of coefficient of friction from 0.7 to 0.55 with the addition of 1% palm methyl ester in the base lubricant. As for the wear, 10% reduction of the wear scar was achieved at the condition of PME10 compared to that at PME0. One of possible explanation for this reduction is the formation of oxidative layer on the contact interface due to the existence of the methyl ester in the lubricant. This result indicates the positive impact of the palm methyl ester as additive for enhancing the performance of conventional lubricant thus requiring further analysis and investigation.